USING MODERN INFORMATION TECHNOLOGY IN THE PRACTICE OF THE SANITARY-EPIDEMIOLOGICAL SURVEILLANCE DURING THE XXII OLYMPIC WINTER GAMES AND XI PARALYMPIC WINTER GAMES IN SOCHI - A. Yu Popova; B. P Kuzkin; Yu. V Demina; V. M Dubyansky; A. N Kulichenko; O. V Maletskaya; O. Kh Shayakhmetov; O. V Semenko; Yu. V Nazarenko; D. S Agapitov; V. M Mezentsev; T. V Kharchenko; et al. (Журнал микробиологии, эпидемиологии и иммунобиологии, 2015)
To improve the sanitary and epidemiological surveillance at the Olympic Games has developed a system of GIS for monitoring objects and situations in the region of Sochi. The system is based on software package ArcGIS, version 10.2 server, with Web-java.lang.Object, Web-server Apach, and software developed in language java. During the execution of the tasks are solved: the stratification of the region of the Olympic Games for the private and aggregate epidemiological risk OCI various etiologies, ranking epidemiologically important facilities for the sanitary and hygienic conditions, monitoring of infectious diseases (in real time according to the preliminary diagnosis). GIS monitoring has shown its effectiveness. Information received from various sources, but focused on one portal. Information was available in real time all the specialists involved in ensuring epidemiological well-being and use at work during the Olympic Games in Sochi.